IMPLEMENTASI POLIGAMI ANTINOMI ANTARA INDIVIDUAL RIGHT DAN SOCIAL RIGHT - Sanyoto, Sanyoto (Jurnal Dinamika Hukum, 2008)
Court of religion have absolute jurisdiction to check and judge polygamy application  and then check the material condition and if its fulfilled, husband as applicant obliged to prove the reason. If he success to prove, so there are polygamous permission, but if he fail to prove the reason of polygamy, so the application will be refused. In application of Polygamy, Religion court give register of polygamous permission in form Pdt G. Verification charged upon husband. Wife have to explain about polygamous permission which given this matter shows importance antinomy between Wife, Husband, and society. Polygamous Implementation in Religion court have done according to existing rule, but for this decision many people is disgruntled because its sacrifice the justice for wife. Kata Kunci: Poligami, Antinomi